Strength-velocity relationship of resisted swimming: a regression analysis - Cuenca-Fernández, F.; Ruiz-Navarro, J. J.; Arellano, R. (ISBS Proceedings Archive (Michigan), 2020)
This study explored how external loads affect semi-tethered resisted swimming (STRS). Twenty national competitive swimmers (age: 18.31 ± 1.42 years) participated in an incremental STRS test. Pearson product-moment correlation coefficients between the load and the swimming variables were obtained, and simple linear regression analyses were applied to evaluate the associations. The results showed that less velocity and acceleration were delivered at high loads (p < 0.001). It increased the velocity fluctuation, affecting the swimming patterns adversely. A decrease in the impulse relative to the load pulled is obtained, especially after 20-30% of the maximal load (R2 = 0.724, p < 0.000). Coaches should reconsider using STRS, as little benefits may be obtained in performance.